Cost-effectiveness analysis of intravenous paricalcitol vs. oral calcitriol in the treatment of hyperparathyroidism secondary to chronic kidney disease - Cardoso, Marilia Mastrocolla de Almeida [UNESP]; Rugolo, Juliana Machado [UNESP]; Lima, Silvana Andrea Molina [UNESP]; de Andrade, Luis Gustavo Modelli [UNESP]; da Silva Pereira Curado, Daniel; Ponce, Daniela [UNESP] (FapUNIFESP (SciELO), 2023)
Introduction: Hyperparathyroidism (SHPT) secondary to chronic kidney disease (CKD) is characterized by high levels of parathyroid hormone (PTH), hyperplasia of the parathyroid glands and cardiovascular disease. Selective and non-selective and selective vitamin D-receptor activators, calcimimetics, are available in the Brazilian market to reduce PTH levels. Objectives: To develop a cost-effectiveness (C/E) and budgetary impact (BI) analysis of intravenous paricalcitol vs. oral calcitriol for patients on dialysis with SHPT, from the perspective of the Brazilian Public Health Care System (SUS). Methodology: We built a decision-tree model to analyze C/E, which considered the outcome of avoided death and a time horizon of 1 year. As for the BI analysis, two scenarios were considered, one of demand and one of epidemiological approach, based on data from the Brazilian Society of Nephrology. Results: The analysis showed that the C/E ratio was R$ 1,213.68 per year, and an incremental effectiveness of 0.032, referring to avoided death. The incremental C/E ratio was R$37,927.50 per death averted by paricalcitol. It was estimated that the incremental BI with the expansion of paricalcitol use will be between R$1,600,202.28 and R$4,128,565.65 in the first year, considering the main and epidemiological scenarios. At the end of 5 years after the expansion of its use, an incremental BI was estimated between R$ 48,596,855.50 and R$ 62,90,555.73. Conclusion: Intravenous paricalcitol has superior efficacy and similar safety to oral calcitriol, reducing the overall mortality of dialysis patients, although it implies a higher cost.
Análise de custo-efetividade do paricalcitol intravenoso vs. calcitriol oral no tratamento do hiperparatireoidismo secundário à doença renal crônica
Keywords: Calcitriol; Cost-Effectiveness Evaluation; Hyperparathyroidism, Secondary; Paricalcitol; Renal Insufficiency, Chronic